2016
DOI: 10.1002/ecy.1552
|View full text |Cite
|
Sign up to set email alerts
|

Stream thermal heterogeneity prolongs aquatic‐terrestrial subsidy and enhances riparian spider growth

Abstract: Abstract. Emerging aquatic insects from streams are important food sources for riparian predators, yet their availability is seasonally limited. Spatial heterogeneity in stream water temperature was found to spatially desynchronize the emergence timing of aquatic insects, and prolong their flight period, potentially enhancing consumer growth. While a mayfly Ephemerella maculata emergence lasted for 12-22 d in local sites along a river, mayflies emerged 19 days earlier from warmer than cooler sites. Therefore, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
35
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(44 citation statements)
references
References 33 publications
4
35
0
Order By: Relevance
“…Stream networks are often investigated in the context of meta-populations and have been shown to confer stability in aquatic ecosystems through the aggregation of dynamics occurring at individual stream reaches (Yeakel et al 2014, Moore et al 2015. Interestingly, we found stream signatures from individual stream reaches could overlap as many as 37 times in some networks and recommend future research assess the degree of asynchrony in aquatic insect emergence among stream reaches within river networks, which can be generated by heterogeneity in stream water temperatures (Uno 2016). Interestingly, we found stream signatures from individual stream reaches could overlap as many as 37 times in some networks and recommend future research assess the degree of asynchrony in aquatic insect emergence among stream reaches within river networks, which can be generated by heterogeneity in stream water temperatures (Uno 2016).…”
Section: Discussionmentioning
confidence: 72%
“…Stream networks are often investigated in the context of meta-populations and have been shown to confer stability in aquatic ecosystems through the aggregation of dynamics occurring at individual stream reaches (Yeakel et al 2014, Moore et al 2015. Interestingly, we found stream signatures from individual stream reaches could overlap as many as 37 times in some networks and recommend future research assess the degree of asynchrony in aquatic insect emergence among stream reaches within river networks, which can be generated by heterogeneity in stream water temperatures (Uno 2016). Interestingly, we found stream signatures from individual stream reaches could overlap as many as 37 times in some networks and recommend future research assess the degree of asynchrony in aquatic insect emergence among stream reaches within river networks, which can be generated by heterogeneity in stream water temperatures (Uno 2016).…”
Section: Discussionmentioning
confidence: 72%
“…), these ranges in temperatures can also be expressed within single rivers (Webb and McLay ) and streams (Baldock et al. , Uno ). This fine‐scale variation can allow poikilotherm consumers to increase their consumption of salmon resources via behavioral thermoregulation (Armstrong et al.…”
Section: Discussionmentioning
confidence: 99%
“…This fine‐scale variation can allow poikilotherm consumers to increase their consumption of salmon resources via behavioral thermoregulation (Armstrong et al. ) and can extend the duration of aquatic subsidies to terrestrial predators such as spiders (Uno ). Our results suggest that in some streams, such as Connecticut Creek, this fine‐scale thermal heterogeneity can increase consumption of salmon resources by generating within‐stream resource waves that alleviate time constraints.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This research spawned a host of additional manipulative experiments excluding or adding prey subsidies for either aquatic or riparian predators (e.g., Paetzold et al 2006;Marczak and Richardson 2007;Eros et al 2012;Sato et al 2016). Additional research that Nakano participated in or inspired has addressed the spatial and temporal heterogeneity of invertebrate subsidies and how it influences the distribution of predators like birds and spiders at different spatial scales (Iwata et al , 2010Iwata 2007;Uesugi and Murakami 2007), and new research has revealed how spatial subsidies of invertebrates stabilize resource fluxes in spatially and thermally heterogeneous river-tributary networks (Uno and Power 2015;Uno 2016). Recent meta-analyses have shown that fish predation reduces adult aquatic insects that emerge to feed terrestrial predators by about 40% (Wesner 2016), and that even though the flux of terrestrial prey to streams is nearly an order of magnitude higher than aquatic prey to riparian zones, the contribution of aquatic prey to terrestrial predators is apparently much higher than of terrestrial prey to aquatic predators (Bartels et al 2012).…”
Section: Linkages Between Terrestrial and Aquatic Ecosystems In Foresmentioning
confidence: 99%